Early post-war Holocaust knowledge and the search for Europe's missing Jews. (1st January 2019) - Lambertz, Jan
ABSTRACT: Lambertz discusses the post-war failure to trace nearly all missing Jews who had been trapped in Europe during the war, which underlines the extent of Nazi violence. Missing person enquiries provide evidence for how Jewish survivors, refugees and immigrants across the globe understood what had happened during the Nazi era. The correspondence arriving in post-war Jewish community offices across Germany in the late 1940s reveals highly fragmentary knowledge of wartime events, both on the part of far-flung former community members and the officials who attempted to assist them.